The anti-von Willebrand factor aptamer ARC1779 increases von Willebrand factor levels and platelet counts in patients with type 2B von Willebrand disease - Jilma-Stohlawetz, Petra; Knöbl, Paul; Gilbert, James C.; Jilma, Bernd (Thrombosis and Haemostasis, 2012)
Blockade of hyperactive von Willebrand factor (VWF) by ARC1779 blunted the platelet drop induced by desmopressin in patients with type 2B von Willebrand disease (VWD). Thus, we hypothesised that ARC1779 may increase VWF levels and correct thrombocytopenia. Three thrombocytopenic patients suffering from type 2B VWD received a loading dose of 0.23 mg/kg ARC1779 followed by 4 μg/kg/min intravenously for 72 hours in a prospective clinical trial. ARC1779 was well tolerated and safe. Plasma concentrations of ARC1779 increased to 76 μg/ml (59–130) leading to an immediate decrease of free VWF A1 domains. VWF/FVIII levels increased as early as 12 h after start of infusion, peaked near the end of infusion, and returned to baseline at follow-up. VWF ristocetin cofactor activity (VWF:RCo) showed a median 10-fold increase 8 hours after end of infusion, while the median VWF-antigen and FVIII increase was less (5-fold and 4-fold, respectively). Most importantly inhibition of hyperactive VWF rapidly increased platelet counts from 40x109/l (38–58 x109/l) to a maximum of 146 x109/l (107–248 x109/l). In conclusion, ARC1779 markedly increases VWF/FVIII levels and most importantly improves or even corrects thrombocytopenia in VWD type 2B patients. This underscores the in vivo potency of ARC1779.
Keywords: von Willebrand disease; thrombocytopenia; aptamer